Management strategies implemented by the principal in relation to the factors associated with the - Hernández Mora, Teresita (2013)
This article responds to the development of the research on the identification of management strategies implemented by the principal in relation to the factors of conflict resolution, motivation and promotion of values, associated with the organizational climate in the educational organizations in study. This research was carried out under a descriptive quantitative approach, with the participation of faculty and staff, as well as principals of educational centers who applied a questionnaire, based on the three variables projected.The results of this study allow to highlight the need of education management professional reinforces the strategies for resolving the conflict through negotiation, mediation and arbitration; also encourages actions to motivate teachers and administrative staff in order to increase their efficiency in the development of work, through recognition, trainings, and interaction among the staff. Regarding the promotion of values, the principal should strengthen strategies for greater involvement of the staff to the school. For this reason, a proposal is made to facilitate the implementation of certain strategies in this regard, especially in conflict resolution, and motivation of the faculty, and administrative staff.